2015
DOI: 10.1152/ajpheart.00417.2015
|View full text |Cite
|
Sign up to set email alerts
|

Sepiapterin prevents left ventricular hypertrophy and dilatory remodeling induced by pressure overload in rats

Abstract: Yoshioka K, Otani H, Shimazu T, Fujita M, Iwasaka T, Shiojima I. Sepiapterin prevents left ventricular hypertrophy and dilatory remodeling induced by pressure overload in rats. Am J Physiol Heart Circ Physiol 309: H1782-H1791, 2015. First published September 25, 2015; doi:10.1152/ajpheart.00417.2015.-Uncoupling of nitric oxide (NO) synthase (NOS) has been implicated in left ventricular (LV) hypertrophy (LVH) and dilatory remodeling induced by pressure overload. We investigated whether administration of sepiap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…Animals (male Wistar rats, 8 weeks old), housed 2 animals per cage, were fed a customized diet containing 13% kcal fat (Envigo [Teklad]) for 10 weeks. Animals were randomized into either control ( n = 5) or sepiapterin ( n = 4) groups, and after the first five weeks, the control group continued on the diet and the sepiapterin group was given food containing sepiapterin at 10 mg/kg body weight ad libitum [ 25 , 29 ]. Food consumption was measured and food replaced twice per week.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Animals (male Wistar rats, 8 weeks old), housed 2 animals per cage, were fed a customized diet containing 13% kcal fat (Envigo [Teklad]) for 10 weeks. Animals were randomized into either control ( n = 5) or sepiapterin ( n = 4) groups, and after the first five weeks, the control group continued on the diet and the sepiapterin group was given food containing sepiapterin at 10 mg/kg body weight ad libitum [ 25 , 29 ]. Food consumption was measured and food replaced twice per week.…”
Section: Methodsmentioning
confidence: 99%
“…Sepiapterin supplementation in diabetic or obese mice resulted in a significant increase in BH 4 , coupled eNOS, and NO production [ 4 , 24 27 ], and diabetic mice fed sepiapterin along with L-citrulline showed inhibition of diabetic cardiomyopathy as well as beneficial effects on eNOS dimerization and NO production [ 28 ]. In a rat model of left ventricle hypertrophy, sepiapterin intake attenuated this condition while increasing NO [ 29 ]. These studies demonstrate that sepiapterin restores BH 4 concentrations, eNOS function, and NO production, resulting in downstream functional benefits in the heart; however, the effects of this BH 4 restoration on mitochondrial function and vasoreactivity in sedentary animals are unexamined.…”
Section: Introductionmentioning
confidence: 99%
“…These results are not surprising given that GCH1 is the first and rate-limiting enzyme in the de novo synthesis of BH 4 12 . A growing body of research indicates that BH 4 is a potential therapeutic target for cardiovascular disease, such as hypertension, myocardial ischemia/reperfusion injury, pressure overload-induced cardiac hypertrophy, and diabetic vascular dysfunction 13, 38, 46, 72, 73 . Despite controversy, BH 4 is generally reported to increase eNOS coupling and phosphorylation, elevate NO production, increase tissue cGMP levels, suppress oxidative/nitrosative stress, improve intracellular Ca 2+ homeostasis, elevates SR Ca 2+ cycling, and inhibit inflammation 13, 38, 46, 74, 75 .…”
Section: Discussionmentioning
confidence: 99%
“…Its mortality rate and the success rate of the model were 7.14% and 85.71%, respectively [15]. Also myocardial fibrosis can be achieved with 17-gauge needle and 6-0 silk suture at the same observation time [16]. Other studies have shown that cardiac hypertrophy, fibrosis, and dysfunction could also be observed 4 weeks after ligating the rat aortic arch with 27-gauge needle and 7-0 silk suture ligature, presenting as an increase in heart weight index (HW/BW), cross-sectional area of left ventricular myocytes, and interstitial collagen content and a decrease in left ventricular eject fraction [17][18][19].…”
Section: Transverse Aortic Constriction Model (Tac)mentioning
confidence: 92%